Avaliação do efeito dos desreguladores endócrinos 17β-estradiol e 17α-etinilestradiol no desenvolvimento da tilápia do nilo (piscis) - Passos Neto, Oscar Pacheco (2020)
Endocrine disruptors are exogenous substances that have the ability to alter one or more functions of the endocrine system with adverse effects on the health of a healthy organism. The main objective of the present work was to evaluate the action of endocrine disrupters 17β-estradiol (E2) and 17α-ethinylestradiol (EE2) in the development of Nile tilapia (Oreochromis niloticus). Four experiments were developed in which the hormonal concentrations of 250, 500 and 1,000 ng L-1 were evaluated with an exposure time of 4 weeks (Experiment 01); 250, 500 and 1,000 μg L-1 with exposure time of 4 weeks (Experiment 02); 160 μg L-1 with exposure time of 4 weeks (Experiment 03) and 160 μg L-1 with exposure time ranging from 1 to 4 weeks (Experiment 04). After the end of the hormonal exposure period, the water in each experimental unit was completely renewed and the individuals were kept in clean water so that they could develop. At the end of this period, the animals were euthanized by stunning on ice, to extract the gonads, prepare the slides and observe under a light microscope. At the end of the experiment it was possible to verify that the hormones and the hormonal concentrations evaluated had a distinct effect on the parameters of zootechnical performance: weight, length, condition factor and survival. Intersex individuals were observed in the treatments with each of the hormones. In addition, malformations were observed in the individuals of the treatments, mainly in the head region. With the data collected in this research it is possible to conclude that the presence of the chemical compounds 17β-estradiol and 17α-ethinylestradiol severely affect the development and sexual differentiation of Nile tilapia.